ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN KAWASAN PERUMAHAN DI KABUPATEN JEMBER - Kun Heruhardjo (Progresif : Media Publikasi Ilmiah, 2021)
Grant (1991) suggests that the strategy of the developers will determine their success in the provision of housing in accordance with the conditions of people's needs in an area. The house is a basic requirement in addition to the food and clothing. Community need a home as a residence. On the other hand, the house serves as a means for public investment and speculation. The purpose of this study was to determine the potential and strategies for real estate development in Jember. Research is qualitative research. This study includes two types of data are primary data and secondary data. Core informants in this study was determined by using the snowball method. Methods of analysis of this research is descriptive analytical method Spradley Model (Etnographic). The results showed Jember District have potential as a region in the development of residential areas which can be seen from the location, land area, population, education facilities. Real estate development strategy in Jember District based on potential areas for residential development to the community. Residential development is focused on the central area of economic activity in Jember District.